A Paradox in Polarization? Cross-pressured Representatives and the Missing Incentive to Moderate. (March 2019) - Toll, Benjamin T.
Members of the public are often left choosing between two extreme candidates who will not represent the moderate, aggregate, public effectively. Cross-pressured members of the U.S. Congress serve a constituency that votes for the opposite party at the national level. If there is any group of representatives that have an incentive to moderate their voting behavior, it is cross-pressured members. In this article, I show that cross-pressured members are more moderate than the average member of their party. This could provide constraints on rampant partisanship in the form of districts that are comfortable electing a representative of one party and voting for the president of the other. However, I show that these members are significantly less likely to be reelected. Thus a paradox exists in which cross-pressured members who moderate their voting behavior are no more likely to be rewarded for behaving the way citizens claim they want to represent.